Estimating Dissipation Rates Associated With Double Diffusion. Issue 15 (27th July 2021) - Middleton, L.; Fine, E. C.; MacKinnon, J. A.; Alford, M. H.; Taylor, J. R.
Abstract: Double diffusion refers to a variety of turbulent processes in which potential energy is released into kinetic energy, made possible in the ocean by the difference in molecular diffusivities between salinity and temperature. Here, we present a new method for estimating the kinetic energy dissipation rates forced by double‐diffusive convection using temperature and salinity data alone. The method estimates the up‐gradient diapycnal buoyancy flux associated with double diffusion, which is hypothesized to balance the dissipation rate. To calculate the temperature and salinity gradients on small scales we apply a canonical scaling for compensated thermohaline variance (or 'spice') on sub‐measurement scales with a fixed buoyancy gradient. Our predicted dissipation rates compare favorably with microstructure measurements collected in the Chukchi Sea. Fine et al. (2018), https://doi.org/10.1175/jpo-d-18-0028.1, showed that dissipation rates provide good estimates for heat fluxes in this region. Finally, we show the method maintains predictive skill when applied to a sub‐sampling of the Conductivity, Temperature, Depth (CTD) data. Plain Language Summary: Understanding the transport of heat in the Arctic Ocean is vital for predicting the fate of sea‐ice in the decades to come. Small‐scale turbulence is an important driver of heat transport and one of the major forms of this turbulence is known as 'double‐diffusive convection'. This is where gradients in temperature and salinity drive turbulence. It is only possible because salinity diffuses significantly slower than temperature, hence the name 'double‐diffusive'. The most direct measurements of ocean mixing require sampling velocity or temperature gradients on scales <1 mm, so‐called microstructure measurements. Here we present a new method for estimating the energy dissipated by double‐diffusive convection using temperature and salinity measurements on larger scales (100s–1000s of metres). We apply the method to a high‐resolution survey of temperature and salinity through a subsurface Arctic eddy and compare the results with simultaneous microstructure measurements. The new technique can reproduce up to 72 % of the observed dissipation rates to within the measurement uncertainty. This suggests the method could be used to estimate the dissipation and so heat fluxes associated with double‐diffusive convection in regions without microstructure measurements. The method also performs well when applied to data sub‐sampled on larger scales. Key Points: We develop a method for estimating dissipation rates due to double‐diffusive convection from temperature and salinity data using an energetic argument The method reproduces the patterns and magnitude of dissipation rates and heat fluxes from microstructure measurements across an arctic eddy The technique performs well even when applied to lower resolution Conductivity, Temperature, Depth (CTD) data